Culture Of Care: Strengthening Workplace Safety And Clinical Governance In Private Hospitals - Rommel Andre M. Amit; Michael A. De La Cerna; Wilbert G. Panerio; Lloyd Matthew C. Derasin (Revista Electronica de Veterinaria, 2024)
Workplace safety culture and clinical governance has increasing gained importance in the provision of safe and quality nursing as well as in upholding the standards of nursing practice. This study utilized a descriptive correlational research design to determine the workplace safety culture and clinical governance among 60 nurses in a private hospital in Lapu-Lapu City. Adopted Safety Culture Questionnaire (SCQ) by Sexton and Clinical Governance Climate Questionnaire (CGCQ) by Freeman were used in this study. The study revealed that majority of the respondents were between 26-40 years old, female, BSN graduates, staff nurses who are assigned in patient care units with 3 – 5 years length of service. The study showed that workplace safety culture was high among nurses in the research environment. In terms of its six dimensions, the study revealed that the respondents have very high safety climate and perceptions of management while experiencing some challenges in terms of working conditions and stress recognition. Additionally, the study revealed clinical governance to be high among nurses especially in terms of proactively managing risk. Furthermore, the study revealed significant relationship between the respondents’ profile and workplace safety culture and clinical governance. Workplace safety culture is positively correlated to clinical governance. Workplace safety culture and clinical governance of nurses are vital component of patient care that will allow nurses to greatly effect positive patient outcomes. Additional research must be undertaken to further increase our understanding on the impact of clinical governance to the workplace safety culture of nurses in a larger scope and population.